The role of financial intermediation in economic growth - Dmytrenko, Oksana (My University, 2014)
Financial intermediaries help efficient allocation of resources by allowing small-scale investors to get the benefits of large-scale investment projects. They do it through screening, fund pooling, risk-pooling, and financial intermediation. Incentive problems The functions described above assume that there is no conflict of interest between the savers and the firms. Additional problems arise when firms have incentives not to reveal all information. All firms do not have the same risk. Savers typically do not have the means to distinguish between high risk and low risk firms. Financial intermediaries can help them do so. It is also costly to monitor the activities of the firm. Individual investors are too small to carry that out. Financial intermediaries can do it on behalf of small investors. These problems are commonly referred to as problems of adverse selection and moral hazard.
Keywords: investment projects; economics; financial intermediation; інвестиційні проекти; економіка; фінансове посередництво; инвестиционные проекты; экономика; финансовое посредничество